IMPLEMENTATION OF KANGAROO MOTHER CARE: Life Sciences-Bioinformatics - PARISA MOHAGHEGHI; ROSHANAK VAKILIAN; SOMAYAE ABDOLLAHI SABET; MOHAMMAD HEIDARZADEH; FOROUZAN AKRAMI; ABBAS HABIBELAHI; NASRIN RASHIDI (International Journal of Life Science and Pharma Research, 2022)
Kangaroo Mother Care [KMC] is an evidence-based approach to reducing mortality and morbidity in preterm infants and as a key intervention package for caring of premature newborns it was designed, planned, and implemented with the practical aim of reforming the low birth weight and premature infants’ health care in Iran during the last 5 years. In this article, the different steps leading to successful implementation of KMC in Iran have been In the first phase of this intervention [2007-2009], KMC national service package was designed as an introduction to KMC, skills development in KMC practice and the management of implementation. In the second phase [2009-2011], advanced skills development for regional steering committee members was sought and the service package was implemented in several tertiary level university hospitals. In the third phase [2011], a nationwide assessment of progress monitoring and a situational analysis of the health-care settings were conducted. Main outcome measures were description of practices, services and facilities for KMC and the effects of KMC on mothers, infants and health team workers.According to monitoring and evaluation in 2011, KMC program has been implemented in 53% of the hospitals and there were favorable evidences of KMC practice in NICUs. Based on the pilot study, neonatal wellbeing at the time of discharge has been improved after intervention [p<0.05]. Eighty-nine percent of mothers pointed out that KMC increased their self-confidence and 84 % of them were satisfied in KMC services. Eighty-four percent of the participating staff believed that KMC program had improved the care giving to the premature newborns and 86 % of them pointed out that they were impressed by better emotional relationship between mother and her child. The results also demonstrated that the main obstacles for implementing KMC were family acceptance and social support.Implementation of the nationwide KMC program is possible and leads to promising outcomes. However, further family and social support is needed for health care system.